ANTIFUNGAL ACTIVITY FROM ETHYLACETATE EXTRACT OF Plumeria alba AGAINST Candida albicans - Murniana Murniana; Israhadi Israhadi; Khairan Khairan; Nurdin Saidi (Universitas Syiah Kuala, 2011)
An investigation on the chemical constituents of plumeria alba has been studied. The compound was extracted from the bark using n-hexane and ethyl acetate as solvent, respectively. The crude was subjected to chromatographic techniques. Isolation and purification of the compound afforded the indole alkaloid. The ethylacetate extract was test to antifungal activity against Candida albicans. The test result sowed inhibition zone of 10 mm on 20% extract concentration.